Diabetes Increases Cryoinjury Size with Associated Effects on Cx43 Gap Junction Function and Phosphorylation in the Mouse Heart - Joseph A. Palatinus; Robert G. Gourdie (Journal of Diabetes Research)
Diabetic patients develop larger myocardial infarctions and have an increased risk of death following a heart attack. The poor response to myocardial injury in the diabetic heart is likely related to the many metabolic derangements from diabetes that create a poor substrate in general for wound healing, response to injury and infection. Studies in rodents have implicated a role for the gap junction protein connexin 43 (Cx43) in regulating the injury response in diabetic skin wounds. In this study, we sought to determine whether diabetes alters Cx43 molecular interactions or intracellular communication in the cryoinjured STZ type I diabetic mouse heart. We found that epicardial cryoinjury size is increased in diabetic mice and this increase is prevented by preinjury insulin administration. Consistent with these findings, we found that intercellular coupling via gap junctions is decreased after insulin administration in diabetic and nondiabetic mice. This decrease in coupling is associated with a concomitant increase in phosphorylation of Cx43 at serine 368, a residue known to decrease channel conductance. Taken together, our results suggest that insulin regulates both gap junction-mediated intercellular communication and injury propagation in the mouse heart.